Analisis Produksi Ikan Tahun 2015 – 2018 (Studi Kasus: Pelabuhan Perikanan Nusantara (PPN) Pemangkat) - Khatimah, Berza Husnul; Harmoko, Harmoko; Novita, Uray Dian (Nekton, 2021)
The fish production on 2015 – 2018 at Pelabuhan Perikanan Nusantara (PPN) Pemangkat made a donation to national production. Fish production at Pelabuhan Perikanan Nusantara (PPN) Pemangkat certainly has dynamics of the fish every year, the causes need to be known. The purpose of this study is to know the conditions of caught fish production at Pelabuhan Perikanan Nusantara (PPN) Pemangkat in 2015 – 2018. The method used in this study is a descriptive method with the kind of research that quantitative and the sample used as data for fish production on 2015 – 2018. The highest catch of fish is in 2018 at 11.041.325 kg and the lowest production of fish occurred in 2015 at 8.574.379 kg. Regression analysis of free variable influence (catch tool, gross tone, trip) on bonded variables (fish production) obtained variable influences are trip and gross tone.